Origins “R” us: investigating the role of R-loops in origin-independent DNA replication - Serdyuk, Anastasia (2024)
The ability of a molecule to self-replicate has been implicated to be the driving force behind the evolution of cellular life from the primordial RNA world. Thus the physicochemical properties of genomic replication are conserved in all three domains of life; Eukaryotes, Bacteria, and Archaea. One of these fundamental properties is the requirement of a terminal hydroxyl group for de novo DNA synthesis. The canonical DNA replication mechanism involves initiation from specific chromosomal sequences – origins of replication. However, an alternative mechanism – recombination dependent replication – has been observed in every domain; the cells are able to replicate without an origin while utilising the 3’ end of a recombination intermediate (directly from R-loops, or indirectly from D-loops) to initiate synthesis from any location on the chromosome. Our understanding of the steps and enzymology of the full replisome assembly from recombination intermediates remains fragmentary. This is due to the small number of culturable model organisms that can replicate in an origin-independent manner. One of these organisms is the halophilic archaeon Haloferax volcanii, which growths faster in the absence of origins, but is easy to culture and is amenable to genetic manipulation. H.volcanii possesses a unique genome architecture: a main chromosome, and 3 mini-chromosomes; each containing multiple origins which can all be deleted except for the origin on pHV3. Moreover, attempted deletions of the pHV3 origin have resulted in genomic rearrangements, where pHV3 is integrated onto the main chromosome. The reasons for that are unknown, except for the low transcription levels on pHV3 detected in previous transcriptomic analyses.